New System to Increase the Useful Life of Exhausted Barrels in Red Wine Aging - Flor-Montalvo, Francisco Javier; Sánchez-Toledo Ledesma, Agustín; Martínez Cámara, Eduardo; Jiménez-Macías, Emilio; Blanco-Fernández, Julio (Foods, 2021)
In recent years, consumers of red wines have demanded aged wines with intense color and a well-integrated fine wood bouquet. Traditionally, wines with these characteristics have been obtained from aging in oak barrels. This type of vinification incurs high costs, including costs associated with the acquisition and use of oak barrels. After five or six vinifications, these barrels are no longer capable of providing an adequate contribution of wood compounds to the wine, because of the exhaustion of their transfer capacity. An alternative to extend the life of these barrels is the introduction of toasted oak staves inside the barrel. In this study, a comparative analysis of the aging of a red wine in new and renewed barrels was developed by inserting toasted staves and analyzing the wine in its different stages, as well as its physical, chemical, and colorimetric characteristics. This study confirms that the use of insert staves anchored in exhausted barrels helps to prolong the useful life of barrels, while maintaining quality assurance.
Keywords: red wine aging; new system of adding wood to wine; barrel oak wood; physicochemical characteristics; oenological parameters; aromatic composition; JCR; Scopus